Analysis of the application of the qi-disability questionnaire to study the quality of life of children with disabilities - Grygus, Igor; Nahorna, Olga (Journal of Education, Health and Sport, 2022)
Assessment of the quality of life of a child with a disability involves studying the physical, psychological, emotional, and social components of his life. Such a multidimensional phenomenon as the assessment of the quality of life of a child with a disability is a personalized and unique survey result, as rather subjective survey indicators are taken into account, which determine the satisfaction of individual needs in the context of the life of a pediatric patient. The QI-Disability questionnaire includes the study of the possibility of communication, psychosocial indicators, physical health, and independence are taken into account. The purpose of the study: analysis of the assessment of the quality of life of children with disabilities of the palliative non-oncology group. Research methods: empirical methods (comparison, description, measurement), theoretical method (axiomatic), general logical methods (analysis, synthesis, generalization), general assessment of quality of life QI-Disability, multivariate regression model. The study was conducted on the basis of the Rivne Educational and Rehabilitation Center «Special Child». 47 (100%) children took part in the study. Research results. The analysis of statistical indicators of children’s disability in the Rivne region during 2015-2021 showed that the number of children with disabilities due to congenital anomalies aged 0-2 years is decreasing: by 73, taking into account the absolute number; due to neurological diseases by 18, taking into account the absolute number; from all causes less by 105; children with disabilities due to congenital anomalies aged 3-6 years decreased: by 143, taking into account the absolute number; due to neurological diseases by 15, taking into account the absolute number; from all reasons less by 189.However, the number of children in this category aged 7 to 14, on the contrary, is increasing: children with disabilities due to congenital anomalies have increased to 191 in absolute terms; due to neurological diseases increased by 63, taking into account the absolute number; 210 more than all the reasons. The study of the quality of life using the QI-Disability survey showed that in the parameter «Social interaction» 388 points were obtained, in the parameter «Negative emotions» – 574 points, in the parameter «Positive emotions» – 237 points, in the domain «Leisure and walks on nature» – 180 points, in the domain «Physical health» – 302 points, in the domain «Independence» – 154 points. In the process of analyzing indicators, a reliable correlation was established between the «Positive Emotions» questionnaire component and other components, which was mathematically confirmed: the dependence is reliable, since the correlation coefficient is 0,921445. Conclusions. The increase in the number of children with disabilities prompts the study of the quality of life of a child of this category in order to find means of rehabilitation to improve the quality of life of the pediatric patient and his family.